2017
DOI: 10.1038/srep38406
|View full text |Cite
|
Sign up to set email alerts
|

Does retinal configuration make the head and eyes of foveate birds move?

Abstract: Animals move their heads and eyes to compensate for movements of the body and background, search, fixate, and track objects visually. Avian saccadic head/eye movements have been shown to vary considerably between species. We tested the hypothesis that the configuration of the retina (i.e., changes in retinal ganglion cell density from the retinal periphery to the center of acute vision-fovea) would account for the inter-specific variation in avian head/eye movement behavior. We characterized retinal configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Bird‐borne cameras have shown that when hunting, falcons orient their head in a position to keep the prey's image at visual angles consistent with use of their temporal fovea . Head and eye movements are also influenced by ganglion cell density across the retina . Birds with a more pronounced rate of change in ganglion cell density across the retina generally show a higher degree of eye movement and higher head movement rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bird‐borne cameras have shown that when hunting, falcons orient their head in a position to keep the prey's image at visual angles consistent with use of their temporal fovea . Head and eye movements are also influenced by ganglion cell density across the retina . Birds with a more pronounced rate of change in ganglion cell density across the retina generally show a higher degree of eye movement and higher head movement rate.…”
Section: Discussionmentioning
confidence: 99%
“…Birds with a more pronounced rate of change in ganglion cell density across the retina generally show a higher degree of eye movement and higher head movement rate. This is likely attributed to the need for aligning the retinal areas of higher visual acuity with objects of interest . Additionally, head and eye movements are affected by the distribution of different types of cones in the retina.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They suggested that the starlings' monocular alternating fixation strategy may facilitate integrating the different types of information gathered by the different portions of each retina. Various avian species are known to have different viewing strategies, depending on the distribution of cells in their retinas [105]. In chickens we know that close objects (20-30 cm in front) are viewed by using the binocular visual field and more distant objects are viewed by using the lateral, monocular visual field [106].…”
Section: Emotion and Eye Use To View A Stimulusmentioning
confidence: 99%